80 Cytological Features of Fine Needle Aspiration of Meningioma on ThinPrep. (11th January 2018) - Viswanathan, Kartik; Sung, Simon; Alperstein, Susan; Hoda, Rana
Abstract: Objectives: Meningiomas represent the most common primary brain tumors arising from the arachnoid villi and can pose a diagnostic challenge in unusual locations. Several studies have described the cytologic features of meningioma on conventional smears (CSs), including whorling pattern, intranuclear grooves and pseudoinclusions, and delicate cytoplasmic extensions. However, little is known of the cytomorphologic features of a meningioma on liquid-based preparations (LBPs). Here, we describe our findings of fine needle aspiration (FNA) of extracranial meningioma on, both CS and ThinPrep (TP) LBP. Methods: An 84-year-old woman presented with a year-long, firm 6.5 cm right sphenotemporal mass with imaging showing extension into surrounding tissues. An FNA of the mass was performed and processed as one air-dried Diff-Quik (DQ)-stained and one alcohol-fixed Pap-stained CS. Residual specimen collected in CytoLyt (TP preservative medium, Hologic, Boxborough, MA) was processed as one Pap-stained TP and one hematoxylin and eosin-stained cell block (CB) slide. Results: The DQ smear showed high tumor cellularity with syncytia and whorls. Cells demonstrated characteristic hyperchromatic nuclei, abundant pale cytoplasm, and terminal wispy extensions. Pap stain showed prominent intranuclear grooves (ING), pseudoinclusions (INI), coarse chromatin, and distinct nucleoli. In comparison, TP showed adequate cellularity despite being processed from residual specimen. Tumor cells were arranged in cohesive three-dimensional clusters with prominent whorls. The cytoplasm ranged from dense to wispy, the latter similar to CS. Nuclear features including ING, INI, coarse chromatin, and nucleoli were preserved. Features on CB were similar. Conclusion: On TP, although cytoplasmic differences were noted, we observed similar architectural and nuclear features of the meningioma seen on the CS. Moreover, residual material was adequate with excellent preservation of cells on TP. Thus, LBPs, such as ThinPrep, can be very valuable in aiding with the diagnosis of meningioma.